Normering i Svenska Akademiens ordlista 1874–1950: principer och resultat - Malmgren, Sven-Göran (LexicoNordica, 2002)
This paper gives a historical survey of the first nine editions (till 1950) of the Swedish Academy Glossary (Svenska Akademiens ordlista, SAOL), a dictionary that provides the Swedish norm of spelling and inflection. Some orthographic and morphological recommendations of the glossary are compared with the real use. The main drawback of the first editions (1874–89) is that they contained very few lemmas, and almost no recent loanwords. From the 1900 edition and onwards, the number of lemmas is quite respectable, but throughout the period the SAOL is characterized by a conservative tendency; there are several examples of spellings and morphological categories – as is shown in the paper – that are recommended by the dictionary long after they have become outdated.